CULTURAL SYMBOLISM BEHIND THE WOVEN MOTIFS OF THE IRANUN IN SABAH: SIMBOLISME BUDAYA DI SEBALIK MOTIF TENUNAN IRANUN DI SABAH - Juita Jaafar Manap; Arba’iyah Abd Aziz, (Jurnal Pengajian Melayu (JOMAS), 2025)
ABSTRACT The Iranun people, an indigenous community native to Sabah, Malaysia, are renowned for their woven textiles that embody a rich cultural heritage. Despite their significance, the symbolic meanings of these motifs remain underexplored, particularly from a semiotic perspective. These woven textiles function not only as utilitarian objects but also as repositories of cultural symbols reflecting the Iranun people’s history, identity, and worldview. This study aims to identify the symbolism and cultural relevance of ten distinct types of Iranun woven textiles. Two primary methods were applied: interviews with skilled weavers and fieldwork involving visual analysis. Data were collected through ethnographic fieldwork, comprising interviews with Iranun master weavers and cultural experts, as well as visual examination of three textile samples. Drawing upon Ferdinand de Saussure’s semiotic theory as the methodological framework, the study interprets the embedded signs and symbols within the motifs and examines their role as signifiers in the broader cultural system. The findings reveal that the motifs encapsulate complex narratives connected to Iranun customs, social hierarchies, and historical interactions, often blending indigenous and external influences. The study contributes to the understanding of Iranun cultural heritage by demonstrating the interplay between visual art and social values. It also recommends future comparative research between the weaving practices of the Iranun in Sabah, Malaysia, and those in Mindanao, Philippines. Keywords: Iranun; cultural symbolism; woven motifs; semiotics; textile heritage ABSTRAK Kaum Iranun ialah komuniti peribumi yang berasal dari Sabah, Malaysia, dan terkenal dengan hasil tekstil tenunan yang melambangkan kekayaan warisan budaya mereka. Walaupun mempunyai kepentingan yang besar, simbolisme motif tenunan kaum ini masih kurang diterokai, khususnya dari perspektif semiotik. Tekstil tenunan bukan sekadar berfungsi sebagai barangan kegunaan harian, malah menjadi wadah simbol budaya yang mencerminkan sejarah, identiti dan pandangan dunia masyarakat Iranun. Objektif kajian ini adalah untuk mengenal pasti simbolisme dan perkaitan budaya bagi sepuluh jenis tekstil tenunan Iranun yang berbeza. Dua kaedah utama digunakan, iaitu temu bual bersama penenun mahir dan kerja lapangan yang melibatkan analisis visual. Data diperoleh melalui pendekatan etnografi yang merangkumi temu bual dengan penenun utama serta pakar budaya Iranun dan analisis visual terhadap tiga sampel tekstil tenunan. Berdasarkan teori semiotik Ferdinand de Saussure sebagai rangka kerja metodologi, kajian ini menghuraikan tanda dan simbol yang tertanam dalam motif serta meneliti peranannya sebagai penanda dalam sistem budaya yang lebih luas. Hasil kajian menunjukkan bahawa motif tenunan Iranun memuatkan naratif yang kompleks berkaitan adat, hierarki sosial, dan interaksi sejarah yang sering menggabungkan pengaruh budaya tempatan serta luar. Kajian ini menyumbang kepada pemahaman warisan budaya kaum Iranun dengan memperlihatkan interaksi antara seni visual dan nilai kemasyarakatan. Kajian turut mencadangkan agar penyelidikan perbandingan dilakukan antara amalan tenunan Iranun di Sabah, Malaysia, dan di Mindanao, Filipina. Kata kunci: Iranun; simbolisme budaya; motif tenunan; semiotik; warisan tekstil